Synthesis and structural characterization of highly tetragonal (1-x)Bi(Zn1/2Ti1/2)-xPbTiO3 piezoceramics - Sharma J.; Pandey R.; Singh A.K. (My University, 2025)
We present here the comprehensive X-ray diffraction (XRD) and dielectric measurement of (1-x)Bi(Zn1/2Ti1/2)O3- xPbTiO3 (BZT-xPT) piezoceramics with x=0.65, 0.70, 0.75 and 0.80. Powder X-ray diffraction data reveals the tetragonal structure (space group P4mm) of BZT-xPT ceramics for all the compositions. © 2013 American Institute of Physics.